2013
DOI: 10.1051/0004-6361/201220423
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive picture of baryons in groups and clusters of galaxies

Abstract: Aims. Based on XMM-Newton, Chandra, and SDSS data, we investigate the baryon distribution in groups and clusters and its use as a cosmological constraint. For this, we considered a sample of 123 systems with temperatures kT 500 = 1.0−9.0 keV, total masses in the mass range M 500 = (∼10 13 −4 × 1070 M , and redshifts 0.02 < z < 1.3. Methods. The gas masses and total masses are derived from X-ray data under the assumption of hydrostatic equilibrium and spherical symmetry. The stellar masses are based on SDSS-DR8… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
83
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(94 citation statements)
references
References 59 publications
(107 reference statements)
8
83
1
2
Order By: Relevance
“…With very few exceptions (Kochanek et al 2003;van Uitert et al 2016), they all consistently measured a relation N ∝ M α , where α < 1.0. This is also consistent with the notion that the stellar mass fraction increases from clusters to group-mass haloes (Gonzalez et al 2013;Laganá et al 2013;Budzynski et al 2014;van der Burg et al 2014). In particular, Viola et al (2015) measured the relation between halo mass and apparent richness for the GAMA groups.…”
Section: 11±007 200supporting
confidence: 90%
“…With very few exceptions (Kochanek et al 2003;van Uitert et al 2016), they all consistently measured a relation N ∝ M α , where α < 1.0. This is also consistent with the notion that the stellar mass fraction increases from clusters to group-mass haloes (Gonzalez et al 2013;Laganá et al 2013;Budzynski et al 2014;van der Burg et al 2014). In particular, Viola et al (2015) measured the relation between halo mass and apparent richness for the GAMA groups.…”
Section: 11±007 200supporting
confidence: 90%
“…The stellar content of cluster galaxies and intracluster light generally represents 10−20% of the total baryonic mass (Lin & Mohr 2004;Gonzalez et al 2007;Andreon 2010Andreon , 2015Mulroy et al 2014). The overall baryon content of galaxy clusters is therefore found to be close to the Universal value (Lin et al 2003;Giodini et al 2009;Laganá et al 2013). Interestingly, these studies observed a general trend of increasing gas fraction (Sun et al 2009;Pratt et al 2009;Lovisari et al 2015) and decreasing stellar fraction (e.g.…”
Section: Introductionmentioning
confidence: 89%
“…The higher velocities of galaxies in high redshift (proto)clusters compared to low redshift clusters 8 , for a constant mass, suggests that the impact of ram pressure stripping should be enhanced, not diminished in distant clusters. Gas at high temperatures dominate the inter-cluster medium (ICM) and the mass budget of low redshift clusters (e.g., Laganá et al 2013). The hot ICM gas has densities of ∼10 −3 to 10 −1 cm −3 , temperatures of ∼10 7 to 10 8 K, and a near unity filling factor (e.g., Sanderson et al 2009).…”
Section: Integrated Schmidt-kennicutt Relationmentioning
confidence: 99%